Doença auto-imune de tireóide e disfunção tireoidiana em pacientes com artrite reumatóide - Gonçalves, Fabrícia Torres (2007)
Previous investigations have suggested an association between autoimmune thyroid disease (AITD), an organ-specific autoimmune disease, and rheumatoid arthritis (RA), a systemic autoimmune disorder. However, this association is controversial because of the great variability of the AITD prevalence in RA patients, the small number of studies and the varying opinions of researchers. The aim of this study is to determine whether there is relationship between AITD and RA and evaluate the correlation of thyroid disease with rheumatoid factor, antinuclear antibodies, and RA activity disease. This case-control study included 189 patients who were consecutively seen in the Rheumatology Clinics of HC-UFU/MG: 72 with RA (ARA criteria, 1987) and 117 with non-autoimmune rheumatic diseases. Blood samples were collected from all subjects for TSH, FT4, anti-TPO and anti-Tg measurement; RA patients were also tested for rheumatoid factor and antinuclear antibodies and the Disease Activity Score using 28 joints count was assessed to measure the disease activity. Thyroid dysfunction was found in 11 (14.86%) and thyroid autoantibodies in 15 (20.83%) RA patients, compared to 18 (15.20%) and 13 (11.11%) of the control group, respectively. There was no correlation between thyroid disease with rheumatoid factor, antinuclear antibodies, disease modifying drugs use, corticosteroids use or RA activity disease. In conclusion, no association could be demonstrated between thyroid disease and RA; this suggests that, at least in some populations, this association does not occur, or it is not strong enough from the epidemiologic point of view to justify the routine thyroid antibodies and thyrotropin tests in all RA patients.